The impact of positive end-expiratory pressure on right ventricular function in patients with moderate-to-severe ARDS: a prospective paired-design study - Xingzheng, Luo; Weiguang, Gu; Quanqiu, Ye; Huifen, Zhou; Zijun, Zheng; Qiming, Zou; Suhua, Yuan; Fu, Zhang; Zhigang, Jian (Frontiers in Medicine, 2024)
Objective To determine the effects of varying positive end-expiratory pressures (PEEPs) on right ventricular function, hemodynamics, oxygenation, and the incidence of acute cor pulmonale (ACP) in patients with moderate-to-severe acute respiratory distress syndrome (ARDS). Methods This prospective paired-design study involved patients with moderate-to-severe ARDS in the ICU. Participants received lung-protective ventilation and hemodynamic monitoring. During the study, mechanical ventilation was administered with PEEPs of 5 cmH2O, 10 cmH2O, and 15 cmH2O, while maintaining an end-inspiratory plateau pressure ≤ 30 cmH2O. Various assessments, including transthoracic echocardiography, cardiac output measurement, and blood gas analysis, were conducted at baseline and after 1 h of ventilation at each PEEP. Subsequently, variations in ventilation oxygenation, echocardiographic parameters, and hemodynamic indicators under different PEEPs were analyzed to explore the potential effects of PEEP on right ventricular function and hemodynamics, as well as the incidence of ACP. Results A total of 317 ARDS patients were screened. Among them, 104 met the diagnostic criteria for moderate-to-severe ARDS, and 52 completed the study. The baseline PEEP of these 52 participants, acquired before commencement, was 11.5 ± 1.7 cmH2O, and the incidence of ACP was 25.0% (13/52). Intensive care unit mortality, overall hospital mortality, and 28-day mortality rates were 19.2% (10/52), 21.2% (11/52), and 32.7% (17/52), respectively. During the study, ACP incidences at PEEPs of 5 cmH2O, 10 cmH2O, and 15 cmH2O were 17.3% (9/52), 21.2% (11/52), and 38.5% (20/52), respectively. Meanwhile, the PaO2/FiO2 ratio improved with increasing PEEP, reaching 162.0 (140.9, 174.0), 171.0 (144.0, 182.0), and 176.5 (151.0, 196) mmHg at PEEPs of 5 cmH2O, 10 cmH2O, and 15 cmH2O, respectively. In addition, higher PEEPs were associated with a slight increase in PaCO2, showing statistically significant differences compared to moderate and low PEEPs. Compared to a PEEP of 5 cmH2O or 10 cmH2O, right ventricular function exhibited substantial changes at 15 cmH2O PEEP, manifested as increased pulmonary artery systolic pressure, enlarged right ventricular end-diastolic area, and decreased tricuspid annular plane systolic excursion, all with significant differences. Conversely, variations in left ventricular end-diastolic area and ejection fraction were not statistically significant. In terms of hemodynamics, increasing PEEP resulted in a decline in cardiac index (CI), with statistically significant differences between different PEEPs. Specifically, compared to the value at a PEEP of 5 cmH2O, the CI at a PEEP of 15 cmH2O decreased by 14.3% (2.63 [2.20, 2.95] vs. 3.07 [2.69, 3.67], p < 0.001). The decline in the stroke volume index with PEEP was more obvious (22.1 [18.4, 27.1] vs. 27.0 [24.2, 33.0], p < 0.001), reaching 18.1%. Additionally, both end-diastolic volume index and extravascular lung water index decreased significantly with increasing PEEP, while the pulmonary vascular permeability index remained unaffected. Conclusion Different PEEPs can affect the incidence of ACP in patients with moderate-to-severe ARDS. High PEEP improves oxygenation and reduces extravascular lung water without significantly affecting the pulmonary vascular permeability index and left ventricular systolic function. Nevertheless, it can cause right ventricular dilation, as well as substantial declines in right ventricular systolic function and CI, thereby causing ACP.